(untitled) (Psychology Travelogs, 2023)
The article is devoted to the peculiarities of the manifestation of resilience in students of higher education institutions. The purpose of the article is a theoretical study of the phenomenon of resilience, clarification of the mechanisms of its occurrence, manifestations and varieties of resilience. We conducted a review of psychological works that were published on this topic, and during the writing of the article we used such methods of theoretical research as analysis and synthesis, and comparison and generalization. The definition of the concept of "resilience" is presented, the peculiarities of manifestations of resilience during the student period are considered. We also considered four trajectories of resilience, such as: "chronic" resilience; "elasticity" (proper resilience); standardized recovery process; adjournment. Resilience mechanisms were considered, which are divided into three groups: resilience mechanisms sensitive to specific dysfunction; general mechanisms; as well as global. According to research by scientists, people with a low level of resilience often react to stressful situations more acutely, avoiding ambiguous stimuli, and individuals with higher levels of resilience can perceive complex situations as interesting without exaggerating or denying their significance. After researching scientific psychological works on this topic, we hypothesized that the potential for increasing the degree of resilience and personal growth can be greater, the greater the impact of the trauma. From the above, it can be concluded that the higher the level of stress in the life of the student during his studies, the lower the intensity of depression or anxiety, as a reaction to the same stress factors, which is extremely important under study time for students, because academic stress and workload in the educational process are long-term and cyclical in nature.